Prognostic significance of neuroepithelial transforming gene 1 in adenocarcinoma of the oesophagogastric junction. - CATHCART, MARY; PIDGEON, GRAHAM; REYNOLDS, JOHN; MULDOON, CIAN (My University, 2014)
BACKGROUND: Neuroepithelial transforming gene 1 (NET1) mediates tumour invasion and metastasis in a number of cancers, including gastric adenocarcinoma. It is an indicator of poor prognosis in breast cancer and glioma. This study examined NET1 expression and its prognostic significance in patients with adenocarcinoma of the oesophagogastric junction (AOG). METHODS: NET1 expression was measured by immunohistochemistry in a tissue microarray, constructed from biobanked tissue collected over a 10-year interval, and linked to a prospectively maintained clinical database. RESULTS: Using the Siewert classification for AOG, type I tumours expressed significantly higher levels of NET1, with lowest expression in type III and intermediate levels in type II (P = 0.001). In patients with AOG type III, NET1-positive patients were more likely to be female (P = 0.043), have advanced stage cancer (P = 0.035), had a higher number of transmural cancers (P = 0.006) and had a significantly higher median number of positive lymph nodes (P = 0.029). In this subgroup, NET1-positive patients had worse median overall (15 versus 23 months; P = 0·025) and disease-free (11 versus 36 per cent; P = 0.025) survival compared with NET1-negative patients. CONCLUSION: Although existing data show differences in clinical and prognostic indices across AOG subtypes, there are no studies showing differences in tumour biology. These data suggest NET1, a known mediator of an aggressive tumour phenotype in a number of gastrointestinal cancers, is expressed differentially across AOG subtypes and may be of prognostic significance in the clinical management of this condition.
PUBLISHED
Keywords: Cancer